Fiscal deficits and stock prices in India: Empirical evidence - Pooja Joshi; Arun Kumar Giri (International Journal of Financial Studies, 2015)
The study aims at examining how fiscal deficits affect the performance of the stock market in India by using annual data from 1988-2012. The study makes use of Ng-Perron unit root tests to check the non-stationarity property of the series; the Auto Regressive Distributed Lag (ARDL) bounds test and a Vector Error Correction Model (VECM) for testing both short and long run dynamic relationships. The variance decomposition (VDC) is used to predict the exogenous shocks of the variables. The findings of the bounds test reveal that the estimated equation and the series are co-integrated. The ARDL results suggest a long run negative relationship exists between budget deficit and stock prices and do not show any significant relationship in the short run. The VECM result shows that fiscal deficits influence the stock price only in the short run. The results of the Variance Decomposition show that stock price movement in the long run is mostly explained by shocks of fiscal deficits. The study implies that the government must adopt appropriate macroeconomic policies to reduce budget deficit, which will result in stock market growth and in turn will lead to the financial development of the country.
Keywords: H62; H68; G10; 330; stock price; fiscal deficit; ARDL; VECM; VDC; India